The Possession of Jesus - Walsh, Richard G. (Biblical interpretation, 2016)
This article reads Jesus’ baptism in Mark as an experience of possession akin to that of the demoniacs. It suggests several possible readings of Mark in light of this baptismal possession: (1) as a story of heavenly rape similar to that of the Lukan Mary’s overshadowing by the spirit; (2) as a story like the possessed of cinematic horror; (3) as a story of a colonial holy warrior’s enthusing possession by the spirit and subsequent dispossession and failure vis-à-vis empire; and (4) as a story of one entrapped by an obsessive script. The readings’ cumulative effect is a different perspective on the Markan Jesus’ first and last words – the announcement of the kingdom of God (Mark 1:14) and his final lament (15:34, 37) – than is common in Markan scholarship. The sayings become descriptions of Jesus’ possession and the subsequent loss of that spirit.